Factors Affecting Cognitive Function in Elderly - Gita Sekar Prihanti; Dwi Wilyani; Achmad Hanif; Afaf Azizah; Atika Rachmania Lilo; Humairoh Nur Permata Imaniah; Nadia Farah Fadhila; Tiara Andini Putri Nastiti; Wahyu Dwi Purnama (Magna Medika)
Background: The number of cognitive impairments in elderly increases gradually every year. The increasing number of elderly can bring various impacts. It has a positive impact if the elderly are in good health. It becomes a negative impact if the elderly have health problems. Mini-Mental Status Examination (MMSE) is a standard and simple test to evaluate cognitive function in elderly.